Quality of Life in Patients with Focal Hyperhidrosis before and after Treatment with Botulinum Toxin A. (6th February 2014) - Kouris, Anargyros; Armyra, Kalliopi; Christodoulou, Christos; Karimali, Polixeni; Karypidis, Dimitrios; Kontochristopoulos, George
Abstract : The aim of this study is to assess the effectiveness of treatment with BTX-A in quality of life of patients suffering from primary focal hyperhidrosis. Materials and Methods . A total of 119 patients (62 females and 57 males) between 18 and 65 years suffering from moderate to severe focal hyperhidrosis were treated with BTX-A. Thirty-nine patients suffered from axillary hyperhidrosis, 47 patients from palmar hyperhidrosis, 12 patients from plantar hyperhidrosis, and 21 patients from palmar and plantar hyperhidrosis. A baseline and posttreated examination of patients 6 months after BTX-A is included. The Hyperhidrosis Disease Severity Scale (HDSS) was chosen to assess the disease severity and the modified Dermatology Life Quality Index was used (DLQI) to assess the quality of life. Results . Quality of life showed a significant improvement after treatment with BTX-A. The total DLQI score resulted significantly lower than the basal value (P < 0.0001 ). The seriousness of hyperhidrosis significantly decreased after the treatment (P < 0.0001 ). In addition, there was notable difference between the posttreatment DLQI scores and pretreatment severity of hyperhidrosis by sex. Conclusions . Treatment with BTX-A led to the reduction of disease severity and improvement of quality of life, while it is a safe, easy to use method with minimal side effects.